Application of Self Assessment Techniques in PAI Learning - Digi Maulana Syah, Antlata (Jurnal Pendidikan Indonesia, 2023)
The main purpose of applying self-assessment techniques is to support or improve learning processes and outcomes. Self-assessment technique is an assessment in which students assess and evaluate the quality of learning or the work they do so that they can identify their weaknesses and strengths in certain learning independently. The self-assessment technique is an assessment method that provides opportunities for students to take responsibility for their own learning. Therefore educators can start the self-assessment process by giving students the opportunity to validate their own thoughts. The approach used in this research is library research. The process involves data collection methods by looking for references in books, dictionaries, journals, document. The results of this study focus on describing: (1) The nature of self-assessment in PAI learning, (2) The urgency of applying self-assessment techniques in PAI learning, (3) Techniques for developing self-assessment instruments in PAI learning.